Impact of Individuals' Disposable Income on Investment of Mutual Funds - Hemant Kothari, Dikshit; Singh, Anjali; Sharma, Rakhi (Journal of Neonatal Surgery, 2025)
This study examines individuals' disposable income on mutual funds investment behaviors, specifically focusing on both the likelihood of investing and the amount invested. Using a quantitative research approach, information was gathered from 102 mutual fund investors residing in Mumbai, India, via structured questionnaires. Various statistical techniques, including Chi- square tests, ANOVA, and logistics regressions with interaction terms, were applied to evaluate the correspondence between discretionary income and investment patterns. The findings indicate that discretionary income does not remarkably influence whether individuals choose to spend in open-end funds. However, it does have a systematically notable effect on the investment amount, with higher income groups allocating a considerable/ concerning size of their disposable income towards open-ended funds. Additionally, Group characteristics that vary in decision-making were analyzed to assess their moderating role. Results show no significant moderating effect, suggesting that the repercussion of disposable income on open-end fund expenditure behavior is consistent across different group characteristics. The study concludes that while a person’s disposable income significantly influences how much they invest, demographic factors like age, gender, or occupation do not have a major impact on their investment decisions. For future research, it is suggested to explore cognitive and social aspects such as financial awareness, risk- taking ability, and overall investment knowledge. This will help in gaining a deeper understanding of the factors that shape open-ended investment behavior.